Studi Tingkat Erodibilitas Tanah Pada EX Disposal Pit A1 PT Kintan Putri Mandiri Subcon PT Anugerah Krida Utama Kecamatan Marangkayu Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Putri Pebrian; Windhu Nugroho; Agus Winarno; Shalaho Dina Devy; Albertus Juvensius Pontus (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Soil is an important component in the natural environment which has an important role in supporting human life and the ecosystem as a whole. One key aspect of soil properties is its erodibility, which determines how susceptible the soil is to erosion. This research aims to assess the level of soil erodibility in the disposal area, which is the location where overburden is deposited in coal mines. Soil erodibility is influenced by a number of factors, including texture, structure, organic matter content, and soil permeability. Laboratory analysis methods are used to measure soil erodibility from samples taken from the disposal area. The results of this research provide a deeper understanding of the potential for erosion in disposal areas and provide a basis for the development of effective erosion control strategies to minimize environmental and mine operational impacts. These findings are important for the coal mining industry in managing the environment sustainably and ensuring the continuity of their operations.